THE PURPOSES AND INTERPRETATIVE ASPECTS OF SELECTED QURANIC STORIES - Hafiz Mohammad Zubair; Ihtasham Ali; Fahmida Kousar (Journal of Religion and Society, 2025)
The Qur’anic stories hold a profound significance as they not only provide moral and spiritual guidance but also serve as timeless lessons for humanity. This study explores the objectives and Tafsir aspects of three selected Qur’anic narratives: the story of Hazrat Adam (peace be upon him), the story of Hazrat Yusuf (peace be upon him), and the story of the Companions of the Cave. The story of Hazrat Adam (peace be upon him) highlights the origins of humanity, the enmity of Satan, and the centrality of repentance in human life. It underscores Allah’s mercy, human fallibility, and the divine purpose of humanity’s role as stewards on Earth. The story of Hazrat Yusuf (peace be upon him) exemplifies patience, wisdom, and forgiveness, portraying a journey from hardship to triumph. It offers a profound message of hope, resilience, and divine justice, particularly inspiring for the youth. The story of the Companions of the Cave reflects unwavering faith, reliance on Allah, and the rejection of worldly distractions. It serves as a powerful reminder of the Day of Judgment and Allah’s omnipotence. From a Tafsir perspective, these narratives reveal the Qur’an’s eloquence, depth, and rhetorical brilliance. The choice of words, structure, and metaphors within these stories invites reflection and contemplation. They address universal human experiences, emphasizing moral principles, the importance of faith, and the ultimate accountability to Allah. This research aims to illuminate the spiritual, ethical, and intellectual dimensions of these Qur’anic stories while highlighting their enduring relevance in contemporary contexts. Keywords: Significance, Spiritual Guidance, Humanity, Judgment, Intellectual Dimensions, Contemporary Contexts.